Letter from Edwin Montell to James Curtis Booth, December 6, 1866 - Montell, Edwin (1866)
Edwin Montell informs James Curtis Booth (1810-1888) that he will send Booth a piece of gold to be coined.
Keywords: Booth, James Curtis, 1810-1888